Control of a Hydro-electromechanical System Using Fractional-order Controllers: A Comparative Study - Daou, Roy Abi Zeid; Moreau, Xavier; Francis, Clovis (Journal of Applied Nonlinear Dynamics, 2026)
This article presents a comparative study of the regulators of a hydro-electromechanical system, composed of two pumps, a uniform tank and a level sensor. Both controllers are fractional orders where the first one is the generalized PID controller and the second one is the CRONE (French acronym: Commande Robuste d’Ordre Non Entier) controller. In a first time, the transfer function of the plant is presented after identification (using the graybox method) and simplification processes. Then, the realization of both regulators is shown where the first controller (generalized PID) is obtained after imposing the regulator model whereas the second one is deduced using the open-loop constraints. At the end, a comparison between the behavior of both controllers is made in the frequency domain around some functional points of the plant as its behavior is nonlinear.